A Grateful Heart Breeds Job Satisfaction: The Effect of Gratitude on Job Satisfaction among Honorary Teachers - Destiana Rachmawati; Nurul Qomariyah (Indonesian Psychological Research, 2024)
Apart from civil servants, which hold the status of full-time and permanent employees, there are other type of government employees, called "honorary or part-time employees". Specifically for teachers, 48 % teachers in Indonesia are honorary teachers. This research aims to examine the influence of gratitude on job satisfaction among honorary teachers. This research uses simple linear regression analysis techniques. This research involved 273 honorary teachers from the Depok City Government who worked in elementary and junior high schools in Depok City as participans. The data analysis indicate a significant effect of gratitude on job satisfaction with (F = 50.908, and R2 = 0.158, with p < 0.01). This result means that gratitude contributes 15.8% in shaping job satisfaction among the teacher. This means that the higher a person is grateful at work, the higher the level of job satisfaction, and vice versa, the lower a person is grateful at work, the lower the level of job satisfaction.